MAIN PROVISIONS OF INNOVATIVE METHODOLOGY STUDY OF ELECTROMAGNETISM IN HIGHER EDUCATION INSTITUTIONS AND SECONDARY EDUCATIONAL INSTITUTIONS - Konoval О.А. (Pedagogy of Higher and Secondary Education, 2003)
Substantive provisions o f an innovational technique o f studying of electromagnetism in the higher and high school are discussed.